Keharmonisan Pernikahan Dalam Perspektif Pengajaran Mempelai - Budi Santosa; Stevanus Parinussa; Wenny Kristiani Waruwu (Shalom: Jurnal Teologi Kristen, 2021)
Abstract: The phenomenon of marital disharmony is very varied. Busy work resulting in a lack of time and attention given to the family. Differences in financial income where when the wife has a salary greater than her husband, thereby reducing respect for her husband, and being an example for the children to their father. The existence of infidelity is also a trigger for the fracture of a marriage. Happy families must have a holy and harmonious marriage blessed by God. The purpose of establishing harmony in a family is not only the formation of a harmonious relationship between husband and wife, but also includes everything related to the welfare and peace of the family. This study uses descriptive qualitative methods with literature review to produce theoretical data on the concept of marital harmony as well as interview and documentation techniques to obtain concrete data about the concept of teaching the bride and groom. The results of the study show that: First, a harmonious Christian marriage will be achieved with the correct understanding and willingness to obey the authority of God's Word. Second, Christian marriage is very beautiful when husband and wife are able to realize and carry out their duties and functions proportionally. Third, the teaching of the bride and groom provides a starting point in marriage as a standard in the family and a picture of Christ's relationship with the church.   Abstrak: Fenomena ketidakharmonisan pernikahan sangat variatif penyebabnya. Kesibukan kerja sehingga kurangnya waktu dan perhatian yang diberikan bagi keluarga. Perbedaan pendapatan finansial dimana ketika isteri memiliki gaji lebih besar dari suami, sehingga mengurangi rasa hormat terhadap suami, dan menjadi contoh anak-anak kepada ayah mereka. Adanya perselingkuhan juga turut menjadi pemicu retaknya pernikahan. Keluarga bahagia harus memiliki pernikahan yang kudus dan harmonis diberkati Tuhan. Tujuan pembentukan keharmonisan dalam sebuah keluarga bukan hanya pembentukan hubungan harmonis suami isteri saja, tetapi didalamnya juga mencakup segala sesuatu yang berhubungan dengan kesejahteraan dan kedamaian keluarga. Penelitian ini menggunakan metode kualitatif deskriptif dengan kajian pustaka untuk menghasilkan data teoretis konsep keharmonisan pernikahan serta teknik wawancara dan dokumentasi guna memeroleh data konkrit tentang konsep pengajaran mempelai. Hasil penelitian menunjukan bahwa: Pertama, pernikahan Kristen harmonis akan tercapai dengan pemahaman yang benar dan kemauan untuk taat terhadap otoritas Firman Allah. Kedua, pernikahan Kristen sangat indah ketika suami isteri mampu menyadari dan menjalankan tugas dan fungsinya secara proporsional. Ketiga, pengajaran mempelai memberikan titik pijak dalam pernikahan sebagai standar dalam keluarga dan gambaran hubungan Kristus dengan jemaat.